2008
DOI: 10.2478/v10012-007-0081-2
|View full text |Cite
|
Sign up to set email alerts
|

A method of diagnosing labyrinth seals in fluid-flow machines

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Location of steam extraction and pressure measurement channels is to be so optimized as to ensure, on the basis of thermodynamic and fluid mechanic relationships, maximum possible accuracy and sensitivity of diagnostic apparature. Role of extraction channels is more thoroughly described in the publication [3].…”
Section: Description Of Packingmentioning
confidence: 99%
“…Location of steam extraction and pressure measurement channels is to be so optimized as to ensure, on the basis of thermodynamic and fluid mechanic relationships, maximum possible accuracy and sensitivity of diagnostic apparature. Role of extraction channels is more thoroughly described in the publication [3].…”
Section: Description Of Packingmentioning
confidence: 99%
“…Labyrinth seals have particular impact on the efficiency of high powergenerating machines. In the paper [1], the impact of the leakage in the internal gland of the steam turbine 13K215 on the power loss was analyzed. It was showed that the power loss resulting from the steam leakage through the internal seal of nominal geometry had achieved approx.…”
Section: Introductionmentioning
confidence: 99%
“…When the service life of the turbine comes to an end (overhaul interval) and the turbine is dismantled, the average height of the gap increases to 1.95 mm [17], as a result of significant wear of seals taking place during turbine operation between overhauls. This effect has a great influence on the thermal turbine efficiency [8]. Ref.…”
Section: Introductionmentioning
confidence: 99%